Prevalence of Traditional and Reverse-Algorithm Syphilis Screening in Laboratory Practice: A Survey of Participants in the College of American Pathologists Syphilis Serology Proficiency Testing Program - Rhoads, Daniel D.; Genzen, Jonathan R.; Bashleben, Christine P.; Faix, James D.; Ansari, M. Qasim (Archives of pathology & laboratory medicine (1976), 2017)
Context.—Syphilis serology screening in laboratory practice is evolving. Traditionally, the syphilis screening algorithm begins with a nontreponemal immunoassay, which is manually performed by a laboratory technologist. In contrast, the reverse algorithm begins with a treponemal immunoassay, which can be automated. The Centers for Disease Control and Prevention has recognized both approaches, but little is known about the current state of laboratory practice, which could impact test utilization and interpretation. Objective.—To assess the current state of laboratory practice for syphilis serologic screening. Design.—In August 2015, a voluntary questionnaire was sent to the 2360 laboratories that subscribe to the College of American Pathologists syphilis serology proficiency survey. Results.—Of the laboratories surveyed, 98% (2316 of 2360) returned the questionnaire, and about 83% (1911 of 2316) responded to at least some questions. Twenty-eight percent (378 of 1364) reported revision of their syphilis screening algorithm within the past 2 years, and 9% (170 of 1905) of laboratories anticipated changing their screening algorithm in the coming year. Sixty-three percent (1205 of 1911) reported using the traditional algorithm, 16% (304 of 1911) reported using the reverse algorithm, and 2.5% (47 of 1911) reported using both algorithms, whereas 9% (169 of 1911) reported not performing a reflex confirmation test. Of those performing the reverse algorithm, 74% (282 of 380) implemented a new testing platform when introducing the new algorithm. Conclusion.—The majority of laboratories still perform the traditional algorithm, but a significant minority have implemented the reverse-screening algorithm. Although the nontreponemal immunologic response typically wanes after cure and becomes undetectable, treponemal immunoassays typically remain positive for life, and it is important for laboratorians and clinicians to consider these assay differences when implementing, using, and interpreting serologic syphilis screening algorithms.